Psychological well-being and cognitive aging in Black, Native American, and White Alzheimer’s Disease Research Center participants - Wyman, Mary F.; Van Hulle, Carol A.; Umucu, Emre; Livingston, Sydnee; Lambrou, Nickolas H.; Carter, Fabu P.; Johnson, Sterling C.; Asthana, Sanjay; Gleason, Carey E.; Zuelsdorff, Megan (Frontiers in Human Neuroscience, 2022)
Psychological well-being is associated with cognition in later life but has not been examined across diverse populations—including minoritized communities at disproportionately high risk of dementia. Further, most previous work has not been able to examine links between specific facets of psychological well-being and performance within distinct cognitive domains that can capture subclinical impairment. Using a well-characterized sample followed through enrollment in an NIH-funded Alzheimer’s Disease Center, we sought to test these associations within three racial groups at baseline. Participants were N = 529 cognitively unimpaired Black, American Indian/Alaska Native (AI/AN), and white middle-aged and older adults (mean age = 63.6, SD = 8.1, range = 45–88 years) enrolled in the Wisconsin Alzheimer’s Disease Research Center’s Clinical Core. Predictors included validated NIH Toolbox Emotion Battery scales assessing positive affect, general life satisfaction, and meaning and purpose. Outcomes included performance on widely used tests of executive functioning and episodic memory. We conducted race-stratified regression models to assess within-group relationships. Black and AI/AN participants reported lower life satisfaction than white participants. Racial disparities were not observed for positive affect or meaning and purpose scores. Across groups, life satisfaction predicted better executive functioning. Similar associations were observed for positive affect in Black and AI/AN samples but not among whites. In general, well-being measures were not related to performance on tests of episodic memory. Our results highlight well-being as a potentially important determinant of late-life cognitive health, particularly executive functioning, that is modifiable if older adults are connected with appropriate resources and supports. Further, psychological well-being may represent a potent target for brain health interventions tailored for Black and Native communities.